PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PERUSAHAAN FARMASI - Bhawa, Ida Bagus Made Dwija; Dewi S., Ni Made Rusmala (E-Jurnal Manajemen, 2015)
This research was conducted at the Pharmaceutical companies listed in Indonesia Stock Exchange (IDX) during 2009-2012. This study uses saturated sumpling where the entire population as a sample of 9 companies which is a pharmaceutical company that terdafar on the Indonesia Stock Exchange during the year 2009-2012.Pengumpulan data was non-participant observation method in which researchers collected data on topic taken. The data analysis technique used is multiple linear regression analysis. Based on the analysis found bahwaukuran company significant negative effect on capital structure, liquidity significant positive effect on capital structure, profitability significant negative effect on capital structure, and business risk is not significant positive effect on capital structure.
Keywords: ukuran perusahaan; likuiditas; profitabilitas; risiko bisnis; struktur modal